How do short sleepers use extra waking hours? A compositional analysis of 24-h time-use patterns among children and adolescents - Aleš Gába; Jan Dygrýn; Nikola Štefelová; Lukáš Rubín; Karel Hron; Lukáš Jakubec; Željko Pedišić (BMC, 2020)
Abstract Background To examine compositional associations between short sleep duration and sedentary behavior (SB), light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA) among children and adolescents. Methods Multi-day 24-h data on sleep, SB, LPA and MVPA were collected using accelerometers among 343 children (8-13 years old) and 316 adolescents (14-18 years old). Children and adolescents with sleep duration of < 9 and < 8 h, respectively, were classified as short sleepers. Robust compositional regression analysis was used to examine the associations between short sleep duration and the waking-time composition. Results Seventy-one percent of children and 75.3% of adolescents were classified as short sleepers. In children, being a short sleeper was associated with higher SB by 95 min/day (p < 0.001) and lower MVPA by 16 min/day (p = 0.002). Specifically, it was associated with a higher amount of time spent in long sedentary bouts (βilr1 = 0.46, 95% confidence interval [CI] = 0.29 to 0.62) and lower amounts of time spent in sporadic SB (βilr1 = − 0.17, 95% CI = -0.24 to − 0.10), sporadic LPA (βilr1 = − 0.09, 95% CI = -0.14 to − 0.04) and sporadic MVPA (βilr1 = − 0.17, 95% CI = -0.25 to − 0.10, p < 0.001 for all), relative to the remaining behaviours. In adolescents, being a short sleeper was associated with a higher amount of time spent in SB by 67 min/day (p = 0.001) and lower LPA by 2 min/day (p = 0.035). Specifically, it was associated with more time spent in sedentary bouts of 1-9 min (βilr1 = 0.08, 95% CI = 0.02 to 0.14, p = 0.007) and 10-29 min (βilr1 = 0.10, 95% CI = 0.02 to 0.18, p = 0.015), relative to the remaining behaviours. Conclusions Among children and adolescents, short sleep duration seems to be highly prevalent and associated with less healthy waking time. Public health interventions and strategies to tackle the high prevalence of short sleep duration among children and adolescents are warranted.